Evaluation of cardiorespiratory effects of an adjunct butorphanol in total intravenous anaesthesia protocol in goats under laparoscopy - Cordeiro, M. F.; Uscategui, R. A. R. [UNESP]; Oliveira, M. E. F. [UNESP]; Dias, D. P. M.; Di Filippo, P. A.; Restan, W. A. S. [UNESP]; Valadao, C. A. A. [UNESP]; Coelho, L. A.; Vicente, W. R. R. [UNESP] (Univ Austral Chile, Fac Ciencias Veterinarias, 2016)
To evaluate the cardiorespiratory effects and postoperative analgesia of a total intravenous anesthesia protocol, twenty-four adult goats were assigned to four experimental groups: G1 and G2 underwent to laparoscopic procedure every 15 days, while G3, and G4 every 30 days. Xylazine (0.05 mg/kg IM) in all animals and butorphanol (0.5 mg/kg IM) in animals of G2 and G4 were used as premedication. Ketamine (2.0 mg/kg IV) anaesthetic induction was performed and subsequently the sheep were intubated and received oxygen (FiO(2) = 1.0). Animals were positioned in a Trendelenburg position and anaesthetic plane maintained by constant infusion of 2 mL/kg/h IV of a solution composed of: 12.5 g of guaiacolate, 25 mg of xylazine and 250 mg of ketamine in 250 mL of 5% dextrose. Haemo-gasometric (pH, PO2 PCO2, cHCO(3)) and clinical parameters (HR, RR, MAP and T), recovery time and postoperative analgesia were evaluated at different times of the anesthetic-surgical procedure. BR, RR, T, pH, PO2, PCO2 and cHCO(3) varied through surgical time and PCO2 was significantly higher in butorphanol treated animals. The studied anaesthetic protocol resulted in a prolonged recovery, clinical hypotension and respiratory acidosis; butorphanol supplementation caused an increase in PaCO2 with no evident improvement of postoperative analgesia. Therefore, the practical application of this protocol indicates a special fluid, ventilation and recovery care. Further studies are needed on the analgesic effect of butorphanol in these situations to allow its indication.
Keywords: butorphanol; xylazine; ketamine; hypotension